2010
DOI: 10.1186/1756-3305-3-123
|View full text |Cite
|
Sign up to set email alerts
|

Description of Hymenolepis microstoma (Nottingham strain): a classical tapeworm model for research in the genomic era

Abstract: BackgroundHymenolepis microstoma (Dujardin, 1845) Blanchard, 1891, the mouse bile duct tapeworm, is a rodent/beetle-hosted laboratory model that has been used in research and teaching since its domestication in the 1950s. Recent characterization of its genome has prompted us to describe the specific strain that underpins these data, anchoring its identity and bringing the 150+ year-old original description up-to-date.ResultsMorphometric and ultrastructural analyses were carried out on laboratory-reared specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 55 publications
0
56
0
1
Order By: Relevance
“…Genomic and transcriptomic data from a laboratory strain of H. microstoma (Platyhelminthes: Cestoda: Cyclophyllidea) maintained in vivo using BALB/c mice and flour beetles (see Cunningham and Olson 2010, for a complete description of the model system) were used to identify orthologs of Wnts and associated signalling components (Table 1). Several Wnt genes were first identified from partial transcripts shot-gun characterised via Roche 454-based sequencing, and representing whole adult and larval worm cDNAs (unpublished data).…”
Section: Genomic Resourcesmentioning
confidence: 99%
“…Genomic and transcriptomic data from a laboratory strain of H. microstoma (Platyhelminthes: Cestoda: Cyclophyllidea) maintained in vivo using BALB/c mice and flour beetles (see Cunningham and Olson 2010, for a complete description of the model system) were used to identify orthologs of Wnts and associated signalling components (Table 1). Several Wnt genes were first identified from partial transcripts shot-gun characterised via Roche 454-based sequencing, and representing whole adult and larval worm cDNAs (unpublished data).…”
Section: Genomic Resourcesmentioning
confidence: 99%
“…bearing hooks should be classified in their own genus (i.e. Rodentolepis ) (see 46). If so, then we expect H. microstoma to be better representative of H. nana than to H. diminuta .…”
Section: Progress In Cestode Genomicsmentioning
confidence: 99%
“…The origin of the strain can be traced back to the original domestication of the species by the C. P. Read laboratory at Texas Rice University in the 1950s (47), making the genome data directly relevant to a large body of previous research based on isolates of this strain. A complete description of the strain and it origins, including a review of its general biology and use as a laboratory model, has been recently published in open access format (46).…”
Section: Progress In Cestode Genomicsmentioning
confidence: 99%
“…Hymenolepis microstoma, a mouse worm, has been used as a model for tapeworm biology studies and teaching due to its easy in vitro proliferation in the laboratory [23]. As previous studies have shown, a small RNA-inducing mechanism is likely to pervasively exist in platyhelminth parasites [17,18].…”
Section: Identification Of Known Mirnas In H Microstomamentioning
confidence: 99%